Efektivitas Pendekatan Behavior dengan Teknik Behavior Contract dalam Mengurangi Perilaku Membolos Siswa Sekolah Menengah Pertama - Dede Teriyani; Linda Fauzia; Muhammad Nur Rifki Hamzah; Rahmah Alifiyah Nawawi; Vany Dwi Putri (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Until now, truancy behavior is still frequently found among students during school hours. This behavior is caused by various factors, such as waking up late, staying up too late at night, feeling tired or sleepy, vehicle problems such as flat tires, lack of motivation to go to school, and other reasons. This problem has become an important concern for school counselors in providing assistance, one of which is through individual counseling services. Students’ participation in the learning process greatly affects the smoothness of learning and the results achieved at school. If truancy behavior continues to be ignored, it can lead to more serious impacts and even increase the risk of students dropping out of school. Therefore, school counselors have an important role in helping overcome this problem with support from students, subject teachers, and parents. One method that can be applied is individual counseling using the behavior contract technique. This technique aims to help students change negative behavior into more disciplined behavior so that truancy habits can be reduced and not repeated again. This study used a qualitative method with interview techniques for data collection. The results of the study showed that individual counseling services using the behavior contract technique were effective in helping overcome truancy behavior among students.